A plasmid-encoded outer membrane protein, TraT, enhances resistance of Escherichia coli to phagocytosis. - Agüero, M E (1984)
The presence of the outer membrane protein TraT, encoded by plasmid R6-5, reduces the sensitivity of Escherichia coli cells to phagocytosis by macrophages. This effect is independent of the bacterial capsule and is more evident in the presence of adsorbed normal human serum. The property of inhibiting phagocytosis is specifically abolished by anti-TraT protein antiserum and anti-TraT immunoglobulin G but not by Fab fragments. These results indicate that the TraT protein is a passive inhibitor of phagocytosis. Inhibition of phagocytosis is produced because the TraT protein antagonizes opsonization by complement, such that C3 deposition is reduced and altered in distribution.